Clinical and laboratory effectiveness of various types of feeding in children of the first year of life with AII - Abdiganieva Dilorom Alisher Qizi; N.U.Tajieva (Genius Journals, 2022)
Acute intestinal infections are a large group of infectious diseases of various etiologies caused by various microorganisms and viruses (salmonella, yersinia, shigella, campylobacteria, rota and noroviruses), with a predominant lesion of the gastrointestinal tract.
Keywords: Acute intestinal infections; microflora; breast milk; exicosis